Prilocaine pharmacokinetics and the influence of vitamin C on methaemoglobin concentrations in tumescent anaesthesia - Bruning, G.; Teichler, A.; Standl, T.; Diederich, A.; Moll, I. (Phlebologie, 2007)
In tumescent local anesthesia high doses of prilocaine are used but valid data on the pharmacokinetics and metabolism of prilocaine during this technique of anesthesia are rare. Patients, methods: In this study plasma prilocaine and methaemoglobin concentrations were measured after subcutaneous injection of prilocaine at doses of 6.69 to 19.21 mg/kg in one hundred patients undergoing varicose vein surgery under tumescent local anesthesia. Half of the patients were randomised to intravenous treatment with 2000 mg ascorbic acid. Glucose-6-phosphate dehydrogenase activity was measured preoperatively. Results: Maximum plasma prilocaine concentrations ranged between 0.14 and 0.86 μg/ml and thus remained below the toxic threshold. Methaemoglobin concentrations ranged between 0.4 and 16.9%. There was no significant effect of vitamin C on the methaemoglobin concentration. Glucose-6-phosphate dehydrogenase activity and methaemoglobin concentrations did not correlate. Conclusions: Tumescent anesthesia with prilocaine at a maximum dose of 20 mg/kg body weight is a safe procedure in varicose vein surgery although the risk of methaemoglobinemia is not reduced by using vitamin C.
Keywords: Ascorbic acid; methaemoglobinaemia; prilocaine; tumescent local anesthesia